2021
DOI: 10.1093/icesjms/fsab002
|View full text |Cite
|
Sign up to set email alerts
|

Ciliate microzooplankton from the Northeastern Gulf of Mexico

Abstract: Microzooplankton mediate a critical juncture of autotrophic and heterotrophic microbial production in the water column. Taxonomic and ecological work on this group has been substantial, yet few reports exist for the offshore waters of the Gulf of Mexico (GOM). This report focuses on protists in the phylum Ciliophora collected at stations spanning the continental shelf in the northeastern GOM. We hypothesized that patterns of spatial distribution across the region would be west–east along the coast, rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Patchiness has not only been demonstrated for phytoplankton, the primary ciliate food, but is also known for ciliate populations (Grattepanche et al 2016 and references therein). Using morphological and molecular tools for identification, mesoscale differences in the taxonomic composition and the feeding type have been reported recently from the South China Sea (Liu et al 2021), the Gulf of Mexico (Snyder et al 2021), and along the New England Shelf in the northwest Atlantic (Grattepanche et al 2016). Ciliate patchiness seems to be generally higher in coastal areas than offshore (Grattepanche et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Patchiness has not only been demonstrated for phytoplankton, the primary ciliate food, but is also known for ciliate populations (Grattepanche et al 2016 and references therein). Using morphological and molecular tools for identification, mesoscale differences in the taxonomic composition and the feeding type have been reported recently from the South China Sea (Liu et al 2021), the Gulf of Mexico (Snyder et al 2021), and along the New England Shelf in the northwest Atlantic (Grattepanche et al 2016). Ciliate patchiness seems to be generally higher in coastal areas than offshore (Grattepanche et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies of ciliate diversity and ecology continued to cover additional habitats on every continent (Antonius & Lipscomb, 2000; Borror, 2007; Caron, 2009a, 2009b; Croquer et al., 2006; Dolan et al., 2012; Edgcomb et al., 2002; Lobban et al., 2011; Lucchesi & Santangelo, 1997; McManus et al., 2004, 2005; Montagnes & Wilson, 2002; Sherr et al., 2007; Snyder et al., 2021; Sonntag et al., 2006). Interest remains high for exploring microbial ecology in extreme environments, finding model protists valuable for rapid assessment of environmental change, revealing cryptic diversity, and examining functional roles of protists in ecological communities, using an abundance of new assessment tools (Abraham et al., 2019; Aguilera, 2013; Caron & Countway, 2009; Caron et al., 2009a, 2009b; Caron et al., 2012; Chao et al., 2006; Dunthorn et al., 2019; Edgcomb, 2016; Edgcomb & Orsi, 2013; Fenchel, 2005; Fenchel & Finlay, 2004, Fenchel & Finlay, 2006; Fernandez‐Leborans, 2001; Ganser et al., 2021; Gooday et al., 2020; Jungblut et al., 2012; Lovejoy et al., 2006; Patterson, 2014; Weisse, 2014; Worden et al., 2006; Xu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The few described Discotrichidae species are not planktonic, but interstitial in sediments, where they consume algae via a characteristic cytopharyngeal basket (Fan et al, 2014; Foissner, 1997). Since NASSO1 was individualized by Boscaro et al (2018) and then incorporated into the PR2 database, it has been reported with relatively high frequencies in coastal and open waters, many times in combination with OLIGO5 (Canals et al, 2020; Duret et al, 2020; Gutiérrez‐Rodríguez et al, 2022; Snyder et al, 2021). NASSO1 ubiquity is also confirmed by a search in metaPR2 v2.0 (Vaulot et al, 2022), which indicates that this clade is present exclusively in marine environments, with 92 V4‐based ASVs from 1523 samples (40% of all the marine samples in the database) collected in photic and aphotic waters of the five oceans and the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Since the OLIGO5 clade was made evident by Boscaro et al (2018), it arose as an abundant and widespread clade, being reported for example in Subtropical and Subantarctic mesopelagic waters of the Pacific (Gutiérrez-Rodríguez et al, 2022), mesopelagic waters of the Scotia Sea (Duret et al, 2020), coastal and open waters of the Gulf of Mexico (Snyder et al, 2021) and diverse stations of the Tara and Malaspina expeditions (Canals et al, 2020). It has been speculated that OLIGO5 may include small bacterivores, histophagous taxa, or parasitic forms, but this remains largely unknown (Snyder et al, 2021).…”
Section: Significant Differences In Assemblage Structure With Depthmentioning
confidence: 99%